Removal of polycyclic aromatic hydrocarbons in a heterogeneous fenton like oxidation system using nanoscale zero-valent iron as a catalyst - Haneef, T. (MDPI AG, 2020)
Oil and gas effluents contains highly toxic and harmful organic pollutants. Therefore, it is necessary to eliminate and/or reduced the concertation of organic pollutants to a technologically acceptable levels before their discharge into water streams. This study investigates the application of nanoscale zero-valent iron (nZVI), and hydrogen peroxide (H2O2) for removal of organic pollutants from real oily produced water. Batch studies were performed and effect of different operating parameters, including concentration of nZVI and H2O2, pH and reaction time were studied. Moreover, optimization of independent variables was performed using central composite design (CCD) in response surface methodology (RSM). The experimental set up provided maximum removal efficiencies of 89.5 and 75.3 for polycyclic aromatic hydrocarbons (PAHs) and chemical oxygen demand (COD), respectively. The optimum values of independent variables such as concentrations of nZVI, and H2O2, contact time and pH were obtained as 4.35 g/L, 1.60 g/L, 199.9 min and 2.9, respectively. Predicted PAHs and COD removal efficiencies at the optimum values of independent variables were found as 89.3 and 75.7, respectively which are in line with the experimental values. The study indicates that application of heterogeneous Fenton like oxidation system using nZVI as a catalyst is an efficient treatment method for removal of organic pollutants from real produced water. Â© 2020 by the authors.